The Impact of Government Spending on Economic Output Provinces In Indonesia - Adhitya Wardhana; Bayu Kharisma; Naimmatul Khairat (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2023)
The purpose of this study is to analyze the impact of government spending on provincial economic output in Indonesia. GRDP is used as a proxy for economic output growth. The object research is the provinces in Indonesia (33 provinces) with the research period 2016-2021. The research method used is Generalized Least Square (GLS). The results showed that the variables of unemployment, government spending on social protection, mean of year's scholling (MYR) and labor had a significant effect on output growth (GRDP), while education spending did not significantly affect output growth. Therefore, the central and regional governments make planning plans on an annual, medium-term and long-term basis with the intention that the role of the existing budget in government can produce targeted output, especially in the education sector.Keyword:Â output growth; government expenditure; generalized least square; GRDP